Clients' experience of therapy and its outcomes in 'good' and 'poor' outcome psychological therapy in a primary care setting: An exploratory study. Issue 4 (25th November 2013) - McElvaney, James; Timulak, Ladislav
Abstract : Aim: The qualitative experience of clients judged by quantitative measures as having 'good' or 'poor' outcome is not often the focus of outcome research. This exploratory study investigates client experience of psychological therapy in an inner‐city primary care centre across two client groups, differentiated on the basis of their outcome scores on quantitative measures. Method: Clients ( N= 11) were allocated to one of two research groups, (a) good outcome ( n= 5), or (b) poor outcome ( n= 6) on the basis of their pre‐ and post‐therapy outcome scores on the Clinical Outcome in Routine Evaluation‐Outcome Measure (CORE‐OM). They participated in a face‐to‐face semi‐structured interview. Data were recorded and analysed using a descriptive and interpretive qualitative method. Results: Both groups had broadly similar experiences of their current therapy although some differences in emphasis emerged. Good outcome clients described a greater sense of empowerment in therapy, commenting on a feeling of equality with their therapist and exhibiting greater autonomy overall. Poor outcome clients valued therapist support and while reporting increased awareness of problematic functioning described a reluctance to engage fully in the therapeutic process. Conclusion: There was very little difference in the qualitative accounts of therapy and its impact by the clients deemed by quantitative pre‐post therapy measurement as either 'good outcome' or 'poor outcome'. There is further research warranted, examining whether clients that seem to benefit from therapy according to standard pre‐post measurement, experience therapy and its impact differently to clients whose pre‐post results suggest that therapy did not work.